Descriptive Memoir of Prime Minister’s Secretariat (1st April, 1956) - Planning Commission (Planning Commission, 1956)
The Prime Minister’s Secretariat assists the Prime Minister in his public activities in that capacity and in his functions as Head of Government within the general framework of established Government procedure. No particular heading or subject of activity allottable to any Ministry is regarded as pertaining to the Prime Minister’s Secretariat, but for purposes like answering questions in the Parliament, it has been found convenient to handle in the Prime Minister’s Secretariat certain very general subjects which could not, on a strict classification, be allotted to any particular Ministry.
Prime Minister's Secretariat